2001
DOI: 10.1046/j.1365-2222.2001.01127.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic proteins are fragmented in low concentrations of sodium hypochlorite

Abstract: We concluded that NaOCl at concentrations commonly used in household products is capable of dramatically affecting allergenic protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…[14][15][16] We investigated whether cat and mite allergen levels in house dust were influenced by the frequency of bleach use. Our findings do not indicate that domestic use of bleach may reduce indoor allergen exposure levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] We investigated whether cat and mite allergen levels in house dust were influenced by the frequency of bleach use. Our findings do not indicate that domestic use of bleach may reduce indoor allergen exposure levels.…”
Section: Discussionmentioning
confidence: 99%
“…13 On the other hand, bleach has been found to be effective in the inactivation of cat and other indoor allergens, probably through the fragmentation of antigenic proteins. 14,15 It has also been shown that bleach is able to reduce skin prick test reactivity to Aspergillus allergens in sensitized individuals when it is used to pretreat mold-contaminated material. 16 It is not clear, however, whether such inactivation of antigenic material has any clinical relevance.…”
mentioning
confidence: 99%
“…When a house is cleaned with bleach, children are not likely to be exposed to high concentrations of chlorine gas or trichloramine simply because they are not directly involved in the cleaning tasks. In that situation, the balance for children -but not necessarily for people doing the cleaning -is clearly in favor of the beneficial effects of chlorine that consist in a decreased risk of asthma and respiratory allergy [14,61,62] as a result of the inactivation of allergens by the hypochlorite [63,64]. Because of the high microbial risks, day care centers require a daily infection of surfaces and objects that infants can be in contact with.…”
Section: Children Living In Places Cleaned With Chlorine Bleachmentioning
confidence: 99%
“…Chlorine-based oxidants can indeed sufficiently denaturate or fragment proteins to completely abolish their immunogenicity. The cat (Fed1) and house dust mite (Der p1) allergens, for instance, have been found to be inactivated by low concentrations of chlorine bleach [63,64].…”
Section: Studies On Human Volunteersmentioning
confidence: 99%
See 1 more Smart Citation